SANKSI HUKUM INDONESIA MENENGGELAMKAN KAPAL ILLEGAL FISHING YANG MENGAMBIL KEKAYAAN LAUT INDONESIA TANPA IZIN DALAM PANDANGAN HUKUM INTERNASIONAL - Irfan Mustofa; Fatma Ulfatun Najicha (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2021)
Lots of Illegal fishing boats have penetrated indonesian waters to takeadvantage by stealing marine assets owned by indonesia. This is of course very detrimental to the indonesian state both from an economic standpoint and a natural conversation point of view. Therefore,this action must be given an appropriate sanction to provide a deterrent effect on the perpetrator of illegal fishing. Besides that,it is also to ward off violations in the border areas of indonesia that could threaten the country”s sovereignty. One of the sanctions of ilegal fishing caught stealing indonesia's marine assets without official permission. With this sanction,there are pros and cons,such as the many protests from the flag state of the ship that sank its ship because it was proven to have stolen the natural wealth of theindonesian state without official permission.